Notice of the Excavation of the Brochs of Yarhouse, Brounaben, Old Stirkoke, Bowermadden, and Dunbeath, in Caithness; with Remarks on the Period of the Brochs; and an Appendix, containing a List of Brochs in Scotland, and Early Notices of many of them (Proceedings of the Society of Antiquaries of Scotland, 1872)
[The journal notes that this paper will be published in the Archaeologia Scotica.]